Being right vs. getting it right: orientation to being recorded in psychotherapeutic interaction as disaffiliative vs. affiliative practice - Franzen, Michael M.; Alder, Marie-Luise; Dreyer, Florian; Köpp, Werner; Buchholz, Michael B. (Frontiers in Psychology, 2023)
This research article examines the practices and implications of the orientation to be recorded in therapeutic interactions. The study examines how the orientation to be recorded differs between affiliative and disaffiliative processes. It highlights that the practices of the orientation to be recorded are context sensitive and adapt to specific circumstances, introducing elements of perception available to both participants. The data is taken from two long-term and one short-term psychotherapy. The study shows that managing orientation to be recorded in a retrospective reference design consistently leads to disaffiliative effects of the sequence. The communicative environment plays a crucial role in interpreting participants' actions, particularly in disaffiliative effect, which can lead to ruptures in the therapeutic alliance. The article emphasizes the importance of considering epistemic imbalances in therapeutic interactions. Furthermore, it suggests that clinicians should be aware of potential disaffiliative rupture cycles as a sensitizing concept to prevent such cycles. The article also discusses the ethical considerations of recording therapeutic sessions, emphasizing the need for informed consent and patient autonomy. The use of video replay as evidence is found to be associated with disaffiliative effect, reflecting a strategy to assert epistemic authority. The study demonstrates that orientation to being recorded can serve as a resource for achieving therapeutic goals, but can also lead to contrasting examples where a shared attentional space fails to emerge. Finally, the article proposes to integrate the findings into the current understanding of how recordings influence therapeutic interactions, emphasizing the observer paradox and the influence of observation 2 This is a provisional file, not the final typeset article on the observed. It suggests that participants' responses to the recording situation can be analyzed as action, emphasizing the need for a communicative turn in therapeutic interactions.This paper aims to further explore the areas of overlap between linguistics and psychotherapy-talk. This common area can be grounded anthropologically (Tomasello, 2014), insofar as human experience becomes describable in terms of publicly observable social actions, rather than participant-interpreted internal mental activities. Accordingly, the present study attempts to focus on phenomena that themselves refer to the quality of observability and public accessibility.